Derivatives: A PowerPlus Picture Book - Hagerty, Kathleen (Review of Financial Studies, 2000)
Journal Article Derivatives: A PowerPlus Picture Book Get access Derivatives: A PowerPlus Picture Book. Mark Rubinstein. Kathleen Hagerty Kathleen Hagerty Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 13, Issue 1, January 2000, Pages 253–256, https://doi.org/10.1093/rfs/13.1.253 Published: 15 June 2015